APLIKASI PUPUK SP-36 DAN PUPUK KANDANG AYAMTERHADAP KETERSEDIAAN DAN SERAPAN FOSFOR SERTA PERTUMBUHAN TANAMAN JAGUNG PADA ULTISOL KWALA BEKALA - Saputra Yakin Hasibuan; MMB Damanik; Gantar Sitanggang (Jurnal Agroekoteknologi, 2014)
The objective of this study about the application of SP - 36 fertilizer and chicken manure onphosphorus availability and uptake and growth of maize on Ultisols taken from Kwala Bekala. Theresearch was conducted in the screen house and Chemical and Soil Fertility Laboratory , Faculty ofAgriculture , University of North Sumatra . This study used randomized block designed whichconsist of 2 factors and 3 replications . The first factor is SP - 36 which consists of 4 levels : 1 . P0 (0 ) , 2 . P1 ( 50 ) , P2 ( 100 ) , P3 ( 150 ) and the second factor is chicken manure : 1 . A0 ( 0 ), 2 . A1( 25 ) , 3 . A2 ( 50 ) , 4 . A3 ( 75 ) . The results showed SP - 36 fertilizer application indicatedsignifican increased soil pH , P-plant uptake , plant height, dry weight and dry root plant, decreasedAl -exchangeable. Application of chicken manure significantly increased soil pH , soil C-organic, P- available soil , P-plant uptake , plant height , dry weight and dry root plant, and decreased Al -exchangeable . Interaction of SP - 36 fertilizer application and chicken manure significantlyincreased the root dry plant .Keywords : SP - 36 fertilizer , chicken manure , soil P - available and P plant uptake